Comparative study of strong anion exchange hypercrosslinked poly(HEMA-co-EGDMA-co-VBC) and strong anion exchange poly(Styrene-co-EGDMA-co-VBC): Synthesis and characterization (Chemical Engineering Research Bulletin, 2017)
Strong anion exchange hypercrosslinked of poly(HEMA-co-EGDMA-co-VBC) (PHEV) and strong anion exchange hypercrosslinked of poly(styrene-co-EGDMA-co-VBC) (PSEV) were prepared via amination reaction with dimethylbutyl amine (DMBA) as the amination agent in dried toluene. The resins were characterized by SEM, FTIR, BET and elemental analysis. SEM results showed that there was no significant change of the particles shape after amination reaction for both strong anion exchange hypercrosslinked PHEV and strong anion exchange hypercrosslinked PSEV. Specific surface area (SSA) of strong anion exchange hypercrosslinked PHEV increase from 1035 m2/g to 1090 m2/g when amination reaction take place. However, SSA of strong anion exchange hypercrosslinked PHEV decreased from 124 m2/g to 27 m2/g. From FTIR spectra, significant drop occurred at 1265 cm-1 band after amination reaction of strong anion exchange hypercrosslinked PSEV but SSA of strong anion exchange hypercrosslinkedPHEV showed slightly significant drop. Elemental analysis showed that nitrogen content of strong anion exchange hypercrosslinked PHEV significantly increase from 0.10% to 1.46% resulted to high IEC value. Meanwhile, nitrogen content in strong anion exchange hypercrosslinked PSEV only showed small increment in nitrogen content from 0.36% to 0.63% led to low IEC value.Chemical Engineering Research Bulletin 19(2017) 96-101